Plasma amyloid-beta levels correlated with impaired hepatic functions: An adjuvant biomarker for the diagnosis of biliary atresia - Lyu, Hongyu; Ye, Yongqin; Lui, Vincent Chi Hang; Wu, Weifang; Chung, Patrick Ho Yu; Wong, Kenneth Kak Yuen; Li, Hung-Wing; Wong, Man Shing; Tam, Paul Kwong Hang; Wang, Bin (Frontiers in Surgery, 2022)
Background: Biliary atresia (BA) is an infantile fibro-obstructive cholestatic disease with poor prognosis. An early diagnosis and timely Kasai portoenterostomy (KPE) improve clinical outcomes. Aggregation of amyloid-beta (Aβ) around hepatic bile ducts has been discovered as a factor for BA pathogenesis, yet whether plasma Aβ levels correlate with hepatic dysfunctions and could be a biomarker for BA remains unknown. Method: Plasma samples of 11 BA and 24 controls were collected for liver function test, Aβ40 and Aβ42 measurement by ELISA. Pearson's chi-squared test or Mann-Whitney U test was performed to assess differences between groups. Correlation between Aβ42/Aβ40 and liver function parameters was performed using Pearson analysis. The area under the receiver-operative characteristic (ROC) curve (area under curve; AUC) was measured to evaluate the diagnostic power of Aβ42/Aβ40 for BA. Diagnostic enhancement was further evaluated by binary regression ROC analysis of Aβ42/Aβ40 combined with other hepatic function parameters. Results: Plasma Aβ42/Aβ40 was elevated in BA patients. Aβ42 displayed a weak positive correlation with GGT (Pearson Correlation=0.349), while there was no correlation for Aβ40 with hepatic functions. Aβ42/Aβ40 was moderately correlated with GGT, TBA, DBIL (Pearson Correlation=0.533, 0.475, 0.480), and weakly correlated with TBIL (Pearson Correlation=0.337). Aβ42/Aβ40 showed an acceptable predictive power for cholestasis (AUC = 0.746 [95% CI: 0.552–0.941], p<0.05). Diagnostic powers of Aβ42/Aβ40 together with hepatic function parameters for cholestasis were markedly improved compared to any indicator alone. Neither Aβ42/Aβ40 nor hepatic function parameters displayed sufficient power in discriminating BA from CC, however, combinations of Aβ42/Aβ40+GGT along with any other hepatic function parameters could differentiate BA from CC-cholestasis (AUC = 1.000, p<0.05) with a cut-off value as 0.02371, -0.28387, -0.34583, 0.06224, 0.01040, 0.06808, and 0.05898, respectively. Conclusion: Aβ42/Aβ40 is a good indicator for cholestasis, but alone is insufficient to distinguish BA from non-BA. However, Aβ42/Aβ40 combined with GGT and one other hepatic function parameter displayed a high predictive power as a screening test for jaundiced neonates who are more likely to be BA, enabling them to early intraoperative cholangiography for BA confirmation and KPE to improve surgical outcomes. However, a multi-centres validation is needed before introduction into daily clinical practice.